The potential immunonutritional role of Parmigiano Reggiano cheese in children with food allergy - Grimaldi, Giusi; Nocerino, Rita; Paparo, Lorella; Cosenza, Linda; Aitoro, Rosita; Trinchese, Giovanna; Amoroso, Antonio; Berni Canani, Roberto (Progress in Nutrition, 2016)
Parmigiano Reggiano (PR) is a ripened cheese with high nutritional value. Throughout ripening the bacteria contained in PR promote an extensive hydrolysis of cow’s milk proteins resulting in peptides that exhibit positive immunoregulatory activities. Additional modulatory activities on immune system are induced by butyrate, a short chain fatty acid widely expressed in PR. These findings suggest a possible immunonutritional role for PR able to stimulate oral tolerance in children with food allergy (FA).